THE TRANSFORMATION OF RELIGIOUS AUTHORITY IN THE ERA OF NEW MEDIA: ANALYZING DISPARITIES IN OPPORTUNITIES BETWEEN FEMALE AND MALE ULAMA IN THE NAHDLATUL ULAMA ONLINE MEDIA - Ma'rufah, Hafidhoh (Jurnal Sosiologi Reflektif, 2023)
The advent of new media has altered the conventional religious authority. Nahdlatul Ulama, one of Indonesia's established religious groups, has been somewhat delayed in harnessing new media platforms, such as its YouTube channel and NU Online website, to disseminate Islamic ideals. Regrettably, NU Online only offers platforms dedicated to the exploration of women's concerns, with female researchers serving as the primary sources of knowledge. This study aims to elucidate the reasons behind the disparity in opportunities between female professors and their male counterparts in the NU media sphere. The study employed a qualitative netnography methodology and examined the data through the lens of Peter L. Berger's Social Construction theory. The findings indicate that the prevailing stereotype of women, namely the perception that women are only supplementary to males, leads to a disparity in the allocation of resources between female and male priests at NU. Female priests, with diverse knowledge and educational capital, should rightfully be recognized as authoritative figures in the realm of religion.Munculnya new media membuat otoritas keagamaan tradisional mengalami pergeseran. Nahdlatul Ulama sebagai salah satu organisasi keagamaan tradisional di Indonesia sedikit terlambat memanfaatkan new media untuk menyebarkan nilai-nilai Islam melalui kanal youtube dan website NU Online. Sayangnya, website NU Online hanya memberi ruang-ruang yang membahas persoalan perempuan saja yang diisi oleh ulama perempuan sebagai narasumber. Penelitian ini mencoba mengungkap kenapa ulama-ulama perempuan ini tidak mendapat kesempatan seluas ulama laki-laki di ruang media NU. Penelitian ini dilakukan dengan menggunakan pendekatan kualitatif netnografi dan dianalisis dengan teori Konstruksi Sosial Peter L. Berger. Hasil penelitian menunjukkan bahwa stereotype terhadap perempuan, yakni bahwa perempuan hanya dipandang sebagai pelengkap laki-laki, menyebabkan positioning ulama perempuan NU belum mendapat porsi yang seimbang dengan ulama laki-laki. Ulama perempuan dengan berbagai modal pengetahuan dan pendidikan sebetulnya layak diposisikan sebagai pihak yang otoritatif dalam keagamaan.